Teacher Career System – Teacher Career Model - Sápi, Zsuzsa (International Journal of Engineering and Management Sciences, 2019)
The Hungarian teacher career model that was introduced on September 1, 2013. In the model the following categories were defined: “Novice Teacher”, “Teacher I”, “Teacher II”, “Master Teacher”, “Researcher Teacher”. At the same time certification and evaluation systems were launched. We introduce the quota and the special requirements set by the Minister of Human Resources.